Digital Sign-Language Model for Inclusive Society 5.0: Model Bahasa Isyarat Digital untuk Masyarakat Inklusif 5.0 - Ekaputra, Muhammad Iqbal Wi’an; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The transition toward Society 5.0 demands accessible technology for all, including people with disabilities. Specific Background: Despite technological progress, digital access for individuals with disabilities remains limited due to low digital literacy and inadequate infrastructure. Gap: Few studies integrate theological concepts with technological innovation to support digital inclusion, especially through sign-language digitalization. Aim: This paper aims to reinterpret the Qur’anic term ar-ramz as a foundation for developing a digital sign-language model using AR and audiobooks. Results: The findings highlight the potential of AR for deaf users through visual optimization and audiobooks for blind users through auditory enhancement. The study also identifies major barriers, including social stigma, digital inequality, and infrastructural limitations. Novelty: This research combines theological interpretation with technological design to propose an inclusive digital model grounded in symbolic interaction. Implications: Policymakers and educators should strengthen digital culture, provide training, and promote accessible technologies to support disabled communities in the era of Society 5.0. Highlights• Digital reinterpretation of ar-ramz• AR and audiobooks for sensory-based inclusion• Inclusive model for Society 5.0 Keywords: Digital Inclusion, AR, Audiobooks, Sign Language, Society 5.0